The effect of learning planning skills and teaching material development skill on teacher teaching skills - Emidar Emidar; Vivi Indriyani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Teacher's teaching skill is the most important indicator in creating successful learning. These teaching skills need to be supported by learning tools so that the learning carried out can be carried out in accordance with the expected goals. These learning tools include the Learning Implementation Plan and Teaching Materials. The teacher before carrying out learning needs to prepare both of these things. The aim of this study was to determine the effect of planning skills and skills on developing teaching materials on teachers' teaching skills. This research uses quantitative research methods using causal associative research, namely research that seeks the influence of one variable (independent) with other variables (dependent). The sample selection technique uses purposive sampling. The number of samples obtained were 32 students. The data analysis method uses SPSS with the Multiple Regression analysis method. The results of the study indicate that planning skills and the ability to create instructional materials have a significant impact on teaching abilities. In addition, planning skills have a significant impact on teaching abilities, whereas developing instructional materials does not. Based on these conclusions, a teacher needs to have skills in planning learning according to the learning model chosen before carrying out learning in class. In addition, to support the learning process, teachers need to prepare teaching materials in the form of teaching materials.